Preliminary Study for Inspecting Moisture Content, Dry Matter Content, and Firmness Parameters of Two Date Cultivars Using an NIR Hyperspectral Imaging System - Ibrahim, Ayman; Alghannam, Abdulrahman; Eissa, Ayman; Firtha, Ferenc; Kaszab, Timea; Kovacs, Zoltan; Helyes, Lajos (Frontiers in Bioengineering and Biotechnology, 2021)
Date Fruits quality attributes assessment and assurance is a key factor in increasing the competitiveness and consumers’ acceptance. The increasing demand for date fruits requires a rapid and automated method for monitoring and analyzing quality attributes of date fruits instead of conventional methods in inspection which limits the production and involves human errors. Moisture content (MC), dry matter content (DMC), and firmness (F) are three important quality attributes for two date cultivars (Khalas and Sukkari) which have been inspected via hyperspectral imaging (HSI) technique based on reflectance mode. Images of intact date fruits at the Tamr mature stage were obtained within the wavelength range of 950 - 1750 nm. Monitor and assessment of MC, DMC, and F (first maximum rupture force (MF, N) were performed using a partial least square regression model. Accurate prediction models were achieved. The results highlight that the coefficients of determination (R2Prediction) are estimated at 0.91 and 0.89 for MC, DMC, and F (N) with the lowest value of the standard error of prediction (SEP) 0.82, 0.81 (%), and 4.12 (N), the residual predictive deviation (RPD) values ranged from 3.65, 3.69, to 3.42 for MC, DMC, and F (N) respectively. The results obtained from this preliminary study indicate the great potential of applying HSI for the assessment of physical, chemical, and sensory quality attributes of date fruits overall the five maturity stages.